Farmers Rate Fertilizer Subsidy Delivery Highly in Periurban Rice Areas: Petani Menilai Penyaluran Pupuk Bersubsidi Sangat Baik di Wilayah Sentra Padi Periurban - Firmansyah Ramadhani; Mirza Andrian Syah; Nuriah Yuliati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Subsidized fertilizer distribution plays an essential role in supporting rice production by ensuring that farmers obtain agricultural inputs through government assistance programs. Specific Background: In Indonesia, the distribution system is evaluated using the